Foreign Trade Company Personnel Management System using SSM Framework - Dong, Junchao; Chen, Tiantian (International Journal of Computing Sciences Research, 2024)
Purpose   – The main purpose of this study is to design and implement an efficient, reliable, and safe personnel management system to improve the human resource management level of foreign trade companies. Method – We chose the SSM framework (Spring + SpringMVC + MyBatis) as the development platform, taking full advantage of its comprehensiveness, maturity, and community support. The system includes an employee information management module, salary and benefits management module, performance evaluation module, and training record module. It also has a responsive design and supports multi-platform access. Results – Through this study, we successfully designed, developed, and implemented a feature-rich personnel management system for foreign trade companies. The system improves employee information accuracy, employee satisfaction, and management efficiency. It allows employees to easily access and manage their personal information while providing management with data on employee performance, compensation structures, and more. Conclusion – Our findings indicate that it is wise to choose the SSM framework as a development platform as it provides a wide range of features and support that help implement the system's requirements. The personnel management system of foreign trade companies plays an important role in improving management efficiency, improving employee satisfaction, providing decision support, and ensuring data security. Recommendations – Future research should focus on further optimizing system performance, improving user experience, exploring data analysis and prediction, implementing mobile applications, and enhancing data security and privacy protection. These improvements will help increase the functionality and value of your personnel management system. Practical Implications – The personnel management system of foreign trade companies based on the SSM framework has extensive practical significance in practical applications. It can improve the competitiveness of foreign trade companies, reduce management costs, and ensure data security and compliance, thus providing strong support for the sustainable development of enterprises. This system also provides valuable experience and reference for research and applications in other similar fields.